Respuesta :
Solution for (y+4)-(y-1)=6y equation:
Simplifying
(y + 4) + -1(y + -1) = 6y
Reorder the terms:
(4 + y) + -1(y + -1) = 6y
Remove parenthesis around (4 + y)
4 + y + -1(y + -1) = 6y
Reorder the terms:
4 + y + -1(-1 + y) = 6y
4 + y + (-1 * -1 + y * -1) = 6y
4 + y + (1 + -1y) = 6y
Reorder the terms:
4 + 1 + y + -1y = 6y
Combine like terms: 4 + 1 = 5
5 + y + -1y = 6y
Combine like terms: y + -1y = 0
5 + 0 = 6y
5 = 6y
Solving
5 = 6y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-6y' to each side of the equation.
5 + -6y = 6y + -6y
Combine like terms: 6y + -6y = 0
5 + -6y = 0
Add '-5' to each side of the equation.
5 + -5 + -6y = 0 + -5
Combine like terms: 5 + -5 = 0
0 + -6y = 0 + -5
-6y = 0 + -5
Combine like terms: 0 + -5 = -5
-6y = -5
Divide each side by '-6'.
y = 0.8333333333
Simplifying
y = 0.8333333333